Racing Translingualism in Composition : Toward a Race-Conscious Translingualism - Rowan, Karen; Do, Tom (Book collections on Project MUSE., 2022)
"Racing Translingualism provides both theoretical and pedagogical reconsiderations of the translingual approach to language diversity by addressing the intersections of race and translingualism. This collection extends the disciplinary conversations about translingualism by foregrounding the role race and racism play in the construction and maintenance of language differences. In doing so, the contributors examine the co-naturalization of race and language in order to theorize a race-conscious translingual praxis. The book begins by offering generative critiques of translingualism, centering on the ways in which the approach's democratic orientation to language avoids issues of race, language, and power and appeals to colorblind racist tropes of equal opportunity. Following these critiques, contributors demonstrate the important intersections of race and translingualism by drawing upon voices typically marginalized by monolingual language ideologies and pedagogies. Finally, Racing Translingualism concludes by attending to the pedagogical implications of a race-conscious translingual praxis in writing and literacy education. Making the case for race-conscious, rather than colorblind, theories and pedagogies, Racing Translingualism offers a unique take on how translingualism is theorized and practiced and moves the field forward through its direct consideration of the links between language, race, and racism. Contributors: Lindsay Albracht, Steven Alvarez, Bethany Davila, Tom Do, Jaclyn Hilberg, Bruce Horner, Aja Martinez, Esther Milu, Stephanie Mosher, Yasmine Romero, Karen Rowan, Rachael Shapiro, Shawanda Stewart, Brian Stone, Victor Villanueva, Missy Watson."--